Sustainable green corridor planning in Tekirdağ, Turkey, using the least-cost path approach - TİGEN, Meltem GÜNEŞ and ÖZCAN, Osman (Edelweiss Applied Science and Technology, 2025)
The rapid expansion of urban areas and the increasing impacts of climate change have intensified pressures on natural ecosystems worldwide. These challenges disrupt biodiversity, fragment habitats, and undermine ecosystem services critical for human well-being. As urbanization accelerates, innovative approaches are needed to maintain connectivity between natural and urban areas while addressing ecological, socio-economic, and recreational needs. This study focuses on Tekirdağ Province as a case study to explore the potential of sustainable green corridor planning in a region facing significant urban and agricultural pressures. Using the Least-Cost Path (LCP) method, spatial data layers including slope, stream networks, transportation routes, and land use were analyzed with GIS to design corridors connecting core natural areas with urban centers. The proposed green corridors prioritize low-gradient terrains and first- and second-order streams, utilizing agricultural lands as multifunctional transition zones to enhance recreational accessibility while preserving natural habitats and minimizing environmental degradation. This study contributes to the literature by demonstrating the effectiveness of the LCP method for local-scale green corridor planning. It demonstrates how this method effectively addresses regional challenges in areas facing the dual pressures of urbanization and agricultural activity. Detailed GIS-based analyses advance data-driven decision-making in corridor design. The proposed network offers a balanced model for conserving natural habitats while accommodating urban demands, contributing to sustainable urban development. Conducted in the Turkish context, this study provides a replicable framework for other regions. Future research should evaluate the long-term sustainability of these corridors, incorporating stakeholder input and real-time data to further optimize connectivity and multifunctionality.